2004
DOI: 10.1128/jvi.78.4.1751-1762.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Expansion of the Residual Tumor Antigen-Specific CD8+T Lymphocytes That Survive Negative Selection in Simian Virus 40 T-Antigen-Transgenic Mice

Abstract: Mice that express the viral oncoprotein simian virus 40 (SV40) large T antigen (T-Ag؉ T cells with high avidity for epitope V survive negative selection in SV11 mice but can be expanded by specific boosting approaches in the tumor bearing host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 78 publications
2
16
0
Order By: Relevance
“…Meanwhile, few studies have focused on T cells that are specifically reactive toward subdominant or immunorecessive tumor epitopes expressed by spontaneous tumors. Previously, our laboratory found that Tag epitope V-specific T CD8 could be expanded from the endogenous T cell repertoire in line 501 SV40 Tag-transgenic mice (18) and line SV11 mice (17). However, the effect on tumor growth was not addressed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, few studies have focused on T cells that are specifically reactive toward subdominant or immunorecessive tumor epitopes expressed by spontaneous tumors. Previously, our laboratory found that Tag epitope V-specific T CD8 could be expanded from the endogenous T cell repertoire in line 501 SV40 Tag-transgenic mice (18) and line SV11 mice (17). However, the effect on tumor growth was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was necessary to immunize specifically against epitope V to detect T cells that recognize this immunorecessive epitope. The residual response to epitope V in SV11 mice is composed primarily of lower avidity T CD8 which recognize Tag epitope V peptide 1,000-to 10,000-fold less efficiently than B6-derived T cells (17). Importantly, booster immunizations expand a population of Tag V-specific clones that effectively lyse wt Tag transformed cells and have avidities similar to T cells derived from B6 mice.…”
mentioning
confidence: 95%
See 3 more Smart Citations